Budgeting and czech companies: connected concepts or two different worlds? - Dokulil, Jiří; Dvorský, Ján; Popesko, Boris (Univerzita Pardubice, 2018)
The presented article is focused on the traditional managerial accounting tool, budgeting, and its application into field of the Czech firms. The study examines the parameters of the budgets in the enterprises operating on the Czech market and investigates factors which influence the usage of the budgeting in these firms. While the first part of this paper summarizes the level of the knowledge in the particular field, the research process is defined in the following step. The main part of the article consists of questionnaire-survey results and hypotheses testing by P-value test.
Keywords: budgeting; planning; perminology; performance measurement; czech firms; M41; M19